Wind-resistant structural optimization of supertall buildings based on high-frequency force balance wind tunnel experiment. (1st December 2021) - Xu, An; Lin, Haidong; Fu, Jiyang; Sun, Weixing
Highlights: A wind-resistant optimal design framework of supertall buildings based on HFFB wind tunnel experiments. A method that transforms all displacement and acceleration constraints into a uniformed natural frequency constraint. The cost of optimized structure increases exponentially with the adopted basic wind pressure value. Abstract: The high-frequency force balance (HFFB) wind tunnel test is one of the most widely used techniques to estimate wind effects on supertall buildings. This paper introduces a wind-resistant optimal design method of supertall buildings based on HFFB wind tunnel experiments. Based on the HFFB wind tunnel test and wind-induced vibration analysis, it provides a reliable and efficient method for structural optimization of supertall buildings with different types of structural members and multiple constraints. Taking advantage of the classic linear mode shape assumption of the HFFB technique, this paper also presents an alternative routine that transforms all different types of constraints into a uniform frequency constraint, which significantly reduces the computational intensity while still offers acceptable accuracy of optimization results. Moreover, the sensitivity of the optimization results to the adopted basic wind pressure value is discussed. The total material cost of the optimized structure increases exponentially with the increase of the basic wind pressure, indicating that the structural costs of supertall buildings are quite sensitive to the adopted basic wind pressure for structural design and its value should be precisely determined by the wind climate analysis of the construction site.